The lost President : A.D. Smith and the hidden history of radical democracy in Civil War America - Dunley, Ruth, 1972- (UnCivil wars, 2019)
"A detective story set against the backdrop of the volatile antebellum era, this socio-cultural biography pieces together methodological inquiry with a jigsaw puzzle composed of secret documents, probate records, court testimony, speeches, correspondence, newspaper coverage and genealogical research in order to tell the story of a man named Smith, of his vision for the United States, and, more generally, of the value of remembering secondary historical characters."--Provided by publishers